Pengembangan Plugin QGIS untuk Menghitung Tingkat Kepadatan Bangunan - Farid Azhari; Fatwa Ramdani; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The continued increase in the human population will continue to be followed by the community's need for a place to live. This causes the use of open land for housing construction, more and more done to meet the needs of human habitation. Every year, big cities experience an increase in built up density which causes new problems, including lack of clean water, flooding, poor public facilities, to land subsidence every year. By utilizing Geographical Information System technology, researchers hope to be able to answer all current and future problems in the future. One of the functions of the Geographical Information System is to identify areas with built up density by calculating the built up index and vegetation index in the area using the open source Quantum Geographic Information System (QGIS) software. The purpose of this research is the development of a QGIS plugin that can help measure the density index of built up in an area using Landsat 8 satellite imagery data. This plugin will be developed using the python programming language because the language is integrated with QGIS and has a package that can be used to calculate indexes on raster data. density of buildings in an area. By doing a confusion matrix test and blackbox testing, this plugin gets a value of 73% and 100% for its functionality value.